Kekuatan fundamental ekonomi Indonesia dan krisis moneter - Syafaruddin Alwi (Universitas Islam Indonesia, 1997)
We must reconsider the statement that the fundamental of Indonesian Economy is strong, at least since currency crisiss occured. Theoretically, the crisis would not be occured if fundamental of Indonesian Economy is strong. Apparately, the crisis has reacted the cripting level and far from being over. Is there anything wrong in economic policy, so we can not solve the problem?